Letter of Credit Disputes from an Arbitration Perspective - Aladwan, Zaid (Hasanuddin Law Review, 2020)
In a recent study, it might not be possible to refer letter of credit fraud cases to arbitration instead of litigation. Alaviâ€™s research suggested that there could be some obstacles, such as obtaining banksâ€™ response and cooperation; the different and high standards of proof of fraud required; and the difficulty in obtaining an injunction. His study answered a question proposed by Blodgett and Mayer as to whether arbitration would ever take place in letter of credit disputes.Â Â This short research paper will answer this question, but from a different angle: whether arbitration will provide more appropriate judgments (award) than litigation regarding letter of credit disputes. This question arises from the writerâ€™s observation that, in the past twenty years, different judgments have been issued for similar disputes.